Sociology: A Disinvitation? - Berger, Peter L. (Sociologija. Mintis ir veiksmas, 2006)
Translation: Peter Berger’s article "Sociology: A Disinvitation?" was first published in a journal Society (1992, vol. 29 (6)). The editorial board of Sociologija. Mintis ir veiksmas is thankful to the State University for permitting to republish this article in Lithuanian.